Establishment the critical control point methodologies of seven major food processes in the catering industry to meet the core concepts of ISO 22000:2018 based on the Taiwanese experience. Issue 6 (19th August 2019) - Chen, Hsinjung; Chen, Yijuan; Liu, Shihlun; Yang, Huiting; Chen, Chinshuh; Chen, Yuhshuen
Abstract: This study focused on significant hazard analysis, the determination and establishment of prerequisite programs, and the role of critical control point (CCP) based on ISO 22000:2018, providing guidelines and experiences related to the incorporation of significant hazard analysis and the use of the CCP decision tree approach to determine and update the possible CCPs of seven primary food processes in the catering industry so as to adhere to the core concept of ISO 22000:2018. Practical Applications: The revised ISO 22000:2018 guideline regarding food safety management systems has been widely implemented by small‐ and medium‐sized catering companies around the world because it suggests appropriate measures for risk management, corporate operations, and the reinforcement of autonomous management that help companies to nip food catering service safety risks in the bud.